SCLU as prognostic biomarker and therapeutic target in osteosarcoma. Issue 1 (1st January 2019) - Ma, Jinfeng; Gao, Weiliang; Gao, Jisheng
ABSTRACT: Osteosarcoma (OS) is the most common primary malignant bone tumor. Secretory apolipoprotein J/clusterin (sCLU) is overexpressed in many cancers; however, its role in OS has not been previously investigated. The objectives of this study were to address this question and also to assess the clinical value of sCLU as a prognostic biomarker and therapeutic target by comparing sCLU expression in human OS (n = 106), normal bone (n = 16), fibrous dysplasia (n = 9), and ossifying myositis (n = 11) tissues and by evaluating the effect of sCLU silencing on OS growth, invasion, and chemosensitivity in vitro and in vivo. We found that sCLU was highly expressed in OS tissue specimens, which was positively correlated with metastatic disease and negatively correlated with response to chemotherapy. sCLU knockdown in KHOS cells inhibited proliferation and invasion and increased apoptosis as well as sensitivity to the chemotherapy drug gemcitabine (Gem). In a mouse xenograft model, sCLU depletion suppressed lung metastasis and enhanced the effects of Gem, thereby slowing KHOS tumor growth. These results indicate that sCLU overexpression is a biomarker for malignant transformation of OS and that therapeutic strategies targeting sCLU may be an effective treatment for OS. Highlights ● Secretory apolipoprotein J/clusterin (sCLU) is overexpressed in osteosarcoma (OS). ● sCLU overexpression is associated with metastasis and chemoresistance. ● Silencing sCLU inhibits metastasis and enhances chemosensitivity in OS cells. sCLU is a biomarker for metastatic OS and a potential therapeutic target.